HENRIK IBSEN’S A DOLL’S HOUSE: WOMAN’S FIGURE REPRESENTATION IN THE VICTORIAN ERA (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2015)
This study aims to analyze womanâ€™s figure representation which was portrayed in Henrik Ibsenâ€™s play A Dollâ€™s House during the Victorian era. The method used is descriptive qualitative. It focused on the words, phrases, sentences, monologues, and dialogues as the data to analyze. The data were also analyzed by using sociological criticism on feminist critique. By using this criticism, the work is analyzed, especially in how Henrik Ibsen depicted womanâ€™s figure in his play. The analysis results in two findings. Womanâ€™s figure representation in this play is portrayed by Noraâ€™s character and by the symbol of â€œdoll.â€ Womanâ€™s figure represented by Noraâ€™s character was complex that she prances about in the first act, behaves desperately in the second, and gains a stark sense of reality during the final of Henrik Ibsen's A Doll's House. In the first, act she represents childlike qualities such as childish, deceptive, obedience, conceited, inconsistent, unadorned, insisted, and dependence. In the second act, she represents a desperate woman by being manipulative, insecure, and seducer. In the final act, she represents mature qualities such as becomes calmer, bolder, and more independent. Womanâ€™s figure represented by the use of â€œdollâ€ as a symbol of woman in this play is that both Nora and the doll are demanding treatment, demanding leadership, and having physical beauty that can give amusement.